"The Death of Deaf Culture or a Biomedical Miracle? Cochlear Implants in Historical Perspective" - Edwards, Rebecca (My University, 2007)
Rebecca Edwards examines the uneasy relationship the American Deaf community has had with assistive technology throughout the nineteenth and twentieth centuries. The medical community has viewed the development of devices to relieve deafnessfrom ear trumpets to hearing aids to cochlear implantsas a sign of progress, and most hearing people have agreed. Some Deaf people have viewed the same progression as a thinly veiled assault on Deaf culture, maintaining that deafness is a cultural condition in need of understanding, not a medical condition in need of alleviation. Edwards probes this nexus of technology, culture, and disability to shed light on both the history of the Deaf as a minority group and the future of disability studies.
Center for the Humanities' A. W. Mellon Workshop / Bodies and the Production of Perversity
Lecture given Thursday, November 30, 2006, in 6191 Helen C. White Hall at 4:00 p.m. Free and open to the public.
Keywords: Mellon workshop; bodies; lecture; deaf culture; biomedical miracle; cochlear implants; technology; disability; Rebecca Edwards; Center for the Humanities